2023
DOI: 10.1111/cup.14523
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repressor GATA binding 1 (TRPS1) immunoexpression in normal skin tissues and various cutaneous tumors

Kohei Taniguchi,
Keisuke Goto,
Hiroki Yabushita
et al.

Abstract: BackgroundTranscriptional repressor GATA binding 1 (TRPS1) is a transcription factor recently shown to play a role in the development of breast and liver cancer. Here, we evaluate TRPS1 immunoexpression in normal skin tissues and various cutaneous tumors.MethodsTRPS1 immunohistochemistry was performed in 109 cases of primary cutaneous tumors and 19 cases of metastatic carcinomas. TRPS1 expression was also evaluated in the normal skin tissues.ResultsThe normal epidermis was TRPS1−. In contrast, the eccrine appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…However, recent studies challenge this notion, revealing that TRPS1 expression extends beyond breast neoplasms. Robust TRPS1 expression has been observed in various cutaneous epithelial neoplasms, including squamous cell carcinomas [ 2 , 3 ], mammary and extramammary Paget diseases [ 2 , 4 ], and adnexal neoplasms [ 3 , 5 , 6 , 7 ]. In dermatopathology, TRPS1 emerges as a valuable tool, particularly in distinguishing primary from secondary extramammary Paget disease, especially when arising in non-perianal cutaneous sites [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies challenge this notion, revealing that TRPS1 expression extends beyond breast neoplasms. Robust TRPS1 expression has been observed in various cutaneous epithelial neoplasms, including squamous cell carcinomas [ 2 , 3 ], mammary and extramammary Paget diseases [ 2 , 4 ], and adnexal neoplasms [ 3 , 5 , 6 , 7 ]. In dermatopathology, TRPS1 emerges as a valuable tool, particularly in distinguishing primary from secondary extramammary Paget disease, especially when arising in non-perianal cutaneous sites [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has revealed a genetic background to this disease, showing that about 85% of poroma cases are related with the following gene fusions: YAP1-MAML2, MAML2-YAP1, YAP1-NUTM1, and WWTR1-NUTM1, which are a consequence of intrachromosomal inversions and translocations [ 8 10 ]. NUT and transcriptional repressor GATA binding 1 (TRPS1) are potential molecular markers of poroma [ 11 , 12 ]. Ultraviolet radiation does not seem to be a key pathogenic factor in poroma development.…”
Section: Introductionmentioning
confidence: 99%